KEPASTIAN HUKUM DALAM PELELANGAN OBJEK HAK TANGGUNGAN SECARA ONLINE - Begiyama Fahmi Zaki (Universitas Lampung, 2016)
Abstract an auction object the formal use of mortgage online in KPKNL arranged in Article 54 paragraph (3) Minister of Finance Regulation Number 106/PMK.06/2013 that the supply of indirect in writing can be done via email or the internet. The auction the object a mortgage via email done through the application of auction email (ALE), both in terms of registration prospective bidders and documents should be equipped with the determination of the winning bidder performed on these applications. Legal certainty in this case that is at the time of the registration process bidders up to set the winning bidder through ALE. This strengthens with the Law Number 11 of 2008 on information and electronic transaction, where Article 5 paragraph (1) described that information electronically and/or document electronic and/or result print is a legal evidence legitimate. The principle of legal certainty of the opinion that an auction had been conducted by KPKNL for the legal protection to parties concerned to an auction. This is in accordance with rights legislation are explained that when debtors injured promise, the holder the mortgage over its own power has the right to sell by auction common. Implementing auction made treatise auction by officials an auction is a certificate authentic in accordance with Article 1867 and 1868 the book the Act of Civil Law. Treatise auction used the seller/the owner goods, buyers and officials auction to maintain and carry out their rights and duties and have the power of perfect in accordance with Article 1 the 32 Minister of Finance Regulation Number 106/PMK.06/2013. Key words: Legal Certainty, The Protection of the Law, Auction, Mortgage Object, Online VolumeAbstrak Penggunaan resmi obyek lelang hipotek secara online di KPKNL diatur dalam Pasal 54 ayat (3) Peraturan Menteri Keuangan Nomor 106/PMK.06/2013 yang pasokan tidak langsung secara tertulis dapat dilakukan melalui email atau internet. Lelang objek hipotek melalui email dilakukan melalui penerapan email lelang (ALE), baik dari segi pendaftaran calon peserta lelang dan dokumen harus dilengkapi untuk penentuan pemenang lelang dilakukan pada aplikasi ini. Kepastian hukum dalam hal ini yaitu pada saat bidder proses pendaftaran hingga mengatur pemenang tender melalui ALE. Ini telah memperkuat dengan Undang-Undang Nomor 11 Tahun 2008 tentang informasi dan transaksi elektronik, di mana Pasal 5 ayat (1) dijelaskan informasi yang elektronik dan/atau dokumen elektronik dan/atau hasil cetak adalah bukti hukum yang sah. Prinsip kepastian hukum berpendapat bahwa lelang telah dilakukan oleh KPKNL untuk perlindungan hukum kepada pihak yang berkepentingan untuk lelang. Hal ini sesuai dengan undang-undang hak dijelaskan bahwa ketika debitur cedera janji, pemegang hipotek atas kekuatan sendiri memiliki hak untuk menjual melalui lelang umum. Menerapkan lelang dibuat risalah lelang oleh pejabat lelang adalah sertifikat otentik sesuai dengan Pasal 1867 dan 1868 Kitab UndangUndang Hukum Perdata. Risalah lelang digunakan penjual/pemilik barang, pembeli dan pejabat lelang untuk mempertahankan dan melaksanakan hak dan kewajiban mereka dan memiliki kekuatan yang sempurna sesuai dengan Pasal 1 Menteri 32 Keuangan Nomor 106/PMK.06/2013. Kata Kunci: Kepastian Hukum, Perlindungan Hukum, Lelang, Objek Hipotek, Online